LEGAL POSITION OF CHILD ADOPTION WITHOUT A JUDGE'S DECISION - Anggie Natasia Theis; Wika Yudha Shanty (Transpublika Publisher, 2022)
This research focuses on adoption cases where prospective adoptive parents carry out the adoption process without obtaining a court decision, which contradicts the stipulations of Article 20 paragraph (1) PP Number 54 of 2007. According to this provision, child adoption must be formally conducted through a court order. The main objectives of this study are to determine the legal status of adoptions conducted without a court order and to examine the legal protection available to adopted children whose adoptions have not undergone a court process, particularly in terms of their rights and obligations within the adoptive family. The research employs the normative legal method, utilizing the statute approach and the case approach to address the problem at hand. A literature study is conducted to collect relevant data, and qualitative methods are employed to analyze the legal materials. The findings of the research highlight that adoptions carried out without a court order lack legal standing, leaving adopted children without adequate legal protection, especially concerning their rights and obligations in the adoptive family. The court's involvement in the adoption process is crucial to establish a proper legal status for the adopted child and to ensure their legal protection, particularly regarding their rights and obligations within the adoptive family.